P097 Abnormal frailty screening is independently associated with both all-cause and disease-related hospital admissions in older patients with inflammatory bowel diseases. (27th May 2021) - Asscher, V; Waars, S; Fens, J; Wieland, M; van der Meulen-de Jong, A; Stuyt, R; Baven-Pronk, M; van der Marel, S; Jacobs, R; Haans, J; Van Deudekom, F; Mooijaart, S; et al.
Abstract: Background: Frailty could be useful for risk stratification in older patients with Inflammatory Bowel Diseases (IBD). However, no prospective evidence is yet available. We aimed to assess how frailty screening associates with hospital admissions and functional and (health related) quality of life (HR)QoL decline. Methods: This is a prospective multicenter cohort study. Consecutive IBD patients aged ≥65 years were included at outpatient departments and infusion centers in six hospitals. Clinical disease activity was assessed through Harvey Bradshaw Index (HBI) or partial Mayo Score (pMS) (remission: HBI<5 or pMS<2), biochemical disease activity by C-reactive protein ≥10 mg/L and/or calprotectin ≥250 µg/g. Frailty screening was performed by Geriatric 8 (G8) questionnaire (abnormal: ≤14). At 18 months, data regarding hospital admissions and mortality were retrieved from medical records and, when possible, verified during follow-up visits. Functional status (Katz Index of Independence in Activities of Daily Living (ADL) and Lawton Instrumental Activities of Daily Living (IADL)) and (HR)QoL (short Inflammatory Bowel Disease Questionnaire and EuroQol-5D) were assessed at baseline and follow-up. Hospital admissions were analyzed with Kaplan Meier and Cox regression, functional and (HR)QoL decline with logistic regression. Analyses were corrected for age and biochemical disease activity. Results: 405 patients were included, median age 70 (IQR 67–74), 85 (21%) clinical disease activity, 93 (23%) biochemical disease activity and 196 (48%) abnormal G8. Until February 2021, 293 (72%) patients were eligible for follow-up: 255 participated in follow-up visits, 38 patients did not (15 not reachable, 16 not willing, 7 died). 74 all-cause and 33 IBD-related hospital admissions occurred. Abnormal G8 was associated with occurrence of both all-cause (adjusted HR 3.9, 95%CI 1.9–7.8, p<.001, Fig. 1) and IBD-related hospital admissions (adjusted HR 4.1, 95% CI 1.4–12.3, p=0.012, Fig. 2). Seven patients died during follow-up; six had abnormal G8. 19 (37%) out of 51 patients with both active biochemical disease and abnormal G8 were hospitalized compared to 4 (14%) out of 29 patients with active disease and normal G8 (p=.026). Abnormal G8 associated with functional (IADL: aOR 3.0, 95% CI 1.3–6.9, P.009, ADL: aOR 1.6, 95% CI 0.7–3.3, p.241) and QoL decline (EQ5D: aOR 2.4, 95% CI 1.4–4.3, p.002), not with HRQoL (sIBDQ: aOR 1.3, 95% CI 0.8–2.2, p=.336). Conclusion: Abnormal frailty screening independently associates with both all-cause and IBD-related hospital admissions and with functional and QoL decline. Therefore, we provide the first prospective evidence for frailty screening as a useful risk stratification tool in IBD.